Model Pendampingan Ibu Rumah Tangga Dalam Pemeriksaan Jentik Untuk Meningkatkan Angka Bebas Jentik - Indah Werdiningsih (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
Dengue fever is a very dangerous disease because it can cause sufferers die within days. The main vector of dengue fever is Aedes mosquito. Prevention of this disease has been done by termination of mosquito transmitter chain by sowing larvicide powder, fogging focus and mosquito nest eradication (PSN). Eradication of mosquito nest is a safer, cheaper and simpler way. Therefore, government policies in dengue vector control are more focused on the program, although this is highly depended on public participation. Other forms of community participation that is expected to increase mosquitoes larvae free score (ABJ) is by engaging housewives who are expected to be able to observe the existence of larvae in their houses, in the hope of increasing ABJ in their respective environments. Counseling with the lecture method has been frequently applied in society. The long term goal of this research is increasing housewives roles in implementing Mosquito Nest Control independently. The specific target of this research is improving mosquitoes larvae free score in Pelem Kidul region so that it can reduce the risk of dengue fever disease cases. The results showed a decrease in the number of Container Index, House index, Breteau Index, Ovitrap Index towards counseling models using pictures (model 1) and lecture method (model 2) in housewives. The most effective counseling model is counseling using picture (model1). It can be concluded that there is a difference between treatment group and before treatment group either in model 1 and model 2.